Pengelolaan Kegiatan Ekstrakurikuler Bidang Keagamaan Dalam Pembinaan Akhlak Siswa - Said Himyari; M. Syahran Jailani; Abd Malik (Center for Religious Studies and Social Empowerment Foundation, 2022)
This article intends to reveal the management of extracurricular activities in the religious field in improving the morals of students at Muhammadiyah Tembilahan Middle School. The research used was qualitative field research (field research) in which the principals and teachers were the respondents. The research results show that; First, the objective condition of Islamic religious education in Tembilahan has not been given ample space for extracurricular teaching, so that all schools use their own initiative to carry out spiritual extracurricular activities by taking advantage of free time outside of compulsory teaching hours. It's just that at this time it is very difficult for some schools to find time, because the hours of compulsory study are so full from morning to evening. Second, the role of the school principal in managing extracurricular activities in the religious field in fostering student morals at Muhammadiyah Tembilahan Junior High School (SMP) is very important. The principal of the Muhammadiyah Junior High School (SMP) in extracurricular activities uses management stages. Third, every activity or program that is carried out always has an influence, be it negative or positive. Artikel ini hendak mengungkap ingin mengungkap pengelolaan ekstrakurikuler bidang keagaamaan dalam meningkatkan akhlak siswa di SMP Muhammadiyah Tembilahan. Penelitian yang digunakan adalah penelitian kualitatif lapangan (field research) di mana yang menjadi responden adalah Kepala Sekolah dan para guru. Hasil penelitian menunjukkan bahwa; Pertama, Kondisi objektif pendidikan agama Islam di Tembilahan belum diberikan ruang yang luas untuk pengajaran ekstrakurikuler, sehingga seluruh sekolah menggunakan inisiatif sendiri melaksanakan kegiatan ekstrakurikuler keruhanian dengan memanfaatkan waktu-waktu kosong di luar jam mengajar wajib. Hanya saja saat ini beberapa sekolah sangat sulit untuk mencari waktu, karena jam belajar wajib yang begitu padat dari pagi hingga sore. Kedua, Peran kepala sekolah dalam pengelolaan kegiatan ekstrakurikuler bidang keagamaan dalam pembinaan akhlak siswa di Sekolah Menengah Pertama (SMP) Muhammadiyah Tembilahan sangat penting. Kepala sekolah Menengah Pertama (SMP) Muhammadiyah dalam kegiatan ekstrakurikuler menggunakan tahapan manajemen. Ketiga, Setiap kegiatan atau program yang dilaksanakan selalu ada yang mempengaruhinya baik itu bersifat negatif atau positif.